Synergic Effect of Motivation and Interest on Achievement of Undergraduate Students of Umar Suleiman College of Education, Gashua - Umoize Stanley; Iyanda Kamoru Ahmed (International Journal of Education Sciences, 2024)
The dwindling performance of students at both internal and external examinations calls for concern among stakeholders in the education enterprise. Numerous studies have been conducted regarding the implications for educational pedagogies. However, redirection of effort towards behavioural management (classroom climate and internal control system) during interaction in the classroom is sin qua non to academic excellence in our schools. The need for educationists in the country to sit-up and think on how to turn around enterprise cannot be overemphasized. A teacher is the pivot on which instructional process revolves the teacher has to glow for his students to shine. A teacher should have a turn grip of his discipline and perhaps more importantly be able to analyse and interpret the needs, desires, and aspirations of the nation as well the community where he lives. Adaralagbe says that a teacher must be a leader, innovator and enlightened parent. As parents, teachers must motivate their students and consider their personal interest in the delivery of instruction through the following ways (i) creation of a learning condition and provision of appropriate learning materials that will bring about enthusiasm in his students. (ii) Creating a student – centred instructional strategy that gives students options with regard to what is learnt, (iii) Allow students to participate actively in knowledge creation while the teacher serves as guidance and facilitator to ensure congruence between knowledge created and public view of the knowledge.
Keywords: Academic excellence; behavioural management; student motivation; student-centred instruction; teacher's role